Effects of wearing modern hijab on cervical range of motion in female students in a private college of Karachi. - Aziz, Khalid; Seyyada Tahniat Al; Fahim, Muhammad Faisal; Khan, Rabia; Shahid, Ghousia (International Journal of Endorsing Health Science Research, 2021)
Background: Cervical spine allow maximum and necessary movements for the functioning of head and sensory organs. Any issue with the flexibility and joint movement can be determined by assessing the cervical range of motion. Cervical range of motion (CROM) assessment is commonly used in clinical practice. The current study aims to find the effects of wearing a hijab on the cervical range of motion compared to the normal cervical range of motions. Methodology: A cross-sectional study was conducted among hijab-wearing female students from Bahria University Medical and Dental College, from November 2019 to January 2020. The study subjects were recruited using a CROM device. Hijab-wearing female students between 18–23 years of age who wear hijab for at least 3 months, with the duration of wearing hijab for at least or at most 6 hours/day were included in the study. Results: A total of 384 students were recruited. Mean Cervical flexion for wearing hijab ≤ 6 hours was 61.06 ± 17.19, and > 6 hours was 55.28 ± 16.09 (p<0.001). Mean extension for wearing hijab ≤ 6 hours was observed to be 41.03 ± 12.89 and for > 6 hours was 37.96 ± 10.94 (p=0.008). Mean Lateral flexion for wearing hijab ≤ 6 hours was 42.66 ± 10.32, and > 6 hours was 38.96 ± 11.01 (p=0.002). While mean right rotation for wearing hijab ≤ 6 hours was 59.50 ± 14.27, and 6 hours was 63.47 ± 14.13 (p=0.010). Moreover, the mean Left rotation for wearing hijab ≤ 6 hours was 64.66 ± 17.86, and >6 hours was 70.58 ± 14.34 (p=0.001). Conclusion: The routine wearing of the hijab affects cervical mobility. Moreover, it is concluded that wearing a hijab for > 6 hours greatly affects the range of the head for movement, by decreasing the cervical range of motion.